EVALUASI KLAIM OVERHEAD PADA PEKERJAAN KONSTRUKSI DALAM TEORI HUKUM KONTRAK: Evaluation of Overhead Claims in Construction Works within the Framework of Contract Law Theory - Huda, Royan Miftahul (Fakultas Hukum, Universitas Trisakti, 2025)
The construction contract for the 500 kV Tanjung Jati – Tx (Ungaran – Pedan) Extra High Voltage Transmission Line (SUTET) is a multi-year agreement that was signed in 2011. However, the actual commencement of work was delayed until the end of 2016 due to late land handover by the Procuring Entity to the Contractor. As a result of this delay, the Contractor encountered significant cash flow difficulties in executing the construction activities. Consequently, the Contractor submitted an overhead claim to the Procuring Entity, despite the fact that the original contract—recognized as the highest governing document—did not explicitly provide for such a claim. This study aims to analyze and evaluate the overhead claim within the context of construction work, based on contract law theory and the applicable regulatory framework in Indonesia. The findings are expected to assist Procuring Entities in addressing contractual issues related to overhead claims more effectively.